Selectivity and Maximum Response of Vibegron and Mirabegron for β3-Adrenergic Receptors - Benjamin M. Brucker, MD; Jennifer King, PharmD; Paul N. Mudd, Jr, PharmD, MBA; Kimberly McHale, PhD (Elsevier, 2022)
ABSTRACT: Background: The β3-adrenergic agonists vibegron and mirabegron have shown favorable safety profiles and efficacy for the treatment of overactive bladder. However, β-adrenergic receptors are also found outside the bladder, which could lead to off-target activity. Objective: This study assessed the selectivity of vibegron and mirabegron for β-adrenergic receptors and the maximal effect and potency for β3-adrenergic receptors. Methods: Functional cellular assays were performed using Chinese hamster ovary-K1 cells expressing β1-, Chinese hamster ovary cells expressing β2-, and human embryonic kidney 293 cells expressing β3-adrenergic receptors. Cells were incubated with vibegron, mirabegron, or control (β1 and β3, isoproterenol; β2, procaterol). Responses were quantified using homogeneous time-resolved fluorescence of cyclic adenosine monophosphate and were normalized to the respective control. Half-maximal effective concentration and maximum response values were determined by nonlinear least-squares regression analysis. Results: Activation of β3-adrenergic receptors with vibegron or mirabegron resulted in concentration-dependent β3-adrenergic receptor responses. Mean (SEM) half-maximal effective concentration values at β3-adrenergic receptors were 2.13 (0.25) nM for vibegron and 10.0 (0.56) nM for mirabegron. At a concentration of 10 µM, β3-adrenergic activity relative to isoproterenol was 104% for vibegron and 88% for mirabegron. Maximum response at β3-adrenergic receptors was 99.2% for vibegron and 80.4% for mirabegron. β1-adrenergic activity was 0% and 3% for vibegron and mirabegron, respectively; β2-adrenergic activity was 2% and 15%, respectively. Conclusions: Vibegron showed no measurable β1 and low β2 activity compared with mirabegron, which showed low β1 and some β2 activity. Both showed considerable selectivity at β3-adrenergic receptors; however, vibegron demonstrated near-exclusive β3 activity and a higher maximum β3 response.